2021
DOI: 10.1007/s12518-021-00378-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of atmospheric discharges in Lubelszczyzna in 2018

Abstract: The aim of the study was to analyse lightning discharges over the Lublin region in 2018 using GIS tools. The methods and systems for detection and location of lightning discharges were presented. The impact of terrain coverage, height above sea level, and location of transceiver stations of mobile operators on the occurrence of discharges was shown. The study provides knowledge of theoretically safer areas and those particularly vulnerable to lightning strikes. Additionally, statistics related to lightning dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Several studies have shown the widespread use and popularity of GIS applications with lightning data (Ali et al, 2018;Biswas et al, 2020;Edirisinghe & Maduranga, 2021;Farukh et al, 2017;Hodanish et al, 2019;Javor et al, 2018;Mammadov et al, 2021;Mishra et al, 2022;Misztal & Siłuch, 2021). However, due to the limitation of information provided by the commercially available LLS, utility found it difficult to work, especially on finding the root cause and correlation of tripping with some other factors such as topography and weather data, thus limiting the research on utilizing GIS for transmission lines' lightning performance evaluation.…”
Section: Figure 1 History Of Lightning Location System In Peninsular ...mentioning
confidence: 99%
“…Several studies have shown the widespread use and popularity of GIS applications with lightning data (Ali et al, 2018;Biswas et al, 2020;Edirisinghe & Maduranga, 2021;Farukh et al, 2017;Hodanish et al, 2019;Javor et al, 2018;Mammadov et al, 2021;Mishra et al, 2022;Misztal & Siłuch, 2021). However, due to the limitation of information provided by the commercially available LLS, utility found it difficult to work, especially on finding the root cause and correlation of tripping with some other factors such as topography and weather data, thus limiting the research on utilizing GIS for transmission lines' lightning performance evaluation.…”
Section: Figure 1 History Of Lightning Location System In Peninsular ...mentioning
confidence: 99%